A Mediator‐Free Electroenzymatic Sensing Methodology to Mitigate Ionic and Electroactive Interferents' Effects for Reliable Wearable Metabolite and Nutrient Monitoring. (16th December 2019) - Cheng, Xuanbing; Wang, Bo; Zhao, Yichao; Hojaiji, Hannaneh; Lin, Shuyu; Shih, Ryan; Lin, Haisong; Tamayosa, Stephanie; Ham, Brittany; Stout, Phoenix; Salahi, Kamyar; Wang, Zhaoqing; et al.
Abstract: Wearable electroenzymatic sensors enable monitoring of clinically informative biomolecules in epidermally retrievable biofluids. Conventional wearable enzymatic sensors utilize Prussian Blue (a redox mediator) to achieve selectivity against electroactive interferents. However, the use of Prussian Blue presents fundamental challenges including: 1) the susceptibility of the sensor response to dynamic concentration variation of ionic species and 2) the poor operational stability due to the degradation of its framework. As an alternative wearable electroenzymatic sensor development methodology to bypass the aforementioned limitations, a mediator‐free sensing interface is devised, comprising of a coupled platinum nanoparticle/multiwall carbon nanotube layer and a permselective membrane. The interface is adapted to develop sensors targeting glucose, lactate, and choline (as examples of informative metabolites and nutrients), showing high degrees of sensitivity, selectivity (against a wide panel of naturally present and diverse interfering species), stability (<6.5% signal drift over 20 h operation), and reliability of sensing operation in sweat samples. By integration within a readout board, a wireless sample‐to‐answer system is realized for on‐body sweat biomarker analysis. This methodology can be adapted to target a wide panel of biomarkers in various biofluids, introducing a new sensor development direction for personal health monitoring. Abstract : Characterization of conventional Prussian Blue‐based wearable enzymatic sensors reveals several fundamental challenges that need to be resolved for reliable operation in complex biofluids. Accordingly, an alternative mediator‐free wearable electroenzymatic sensing system is devised, where the experimental results indicate the high degrees of sensitivity, selectivity, and stability of the developed sensors for wireless biofluid analysis.